2021
DOI: 10.1128/msystems.00252-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Reveals Thermal Adaptation and a High Metabolic Diversity in “ Candidatus Bathyarchaeia”

Abstract: Ca . Bathyarchaeia MAGs from terrestrial hot spring habitats are poorly revealed, though they have been studied extensively in marine ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 92 publications
(115 reference statements)
10
43
0
Order By: Relevance
“…This suggests that Thermocrinis -affiliated bacteria may not have nitrogen fixation ability in some hot springs. This phenomenon can be explained by the fact that some Thermocrinis species living in YNP hot springs may obtain nifH gene from coexisting diazotrophs such as Hydrogenobacter through horizontal gene transfer that was speculated to occur among diazotrophs ( Koirala and Brözel, 2021 ) or prokaryotes in hot springs ( Zhu et al, 2019 ; Li et al, 2021 ; Qi et al, 2021 ). In addition, there was one unique Aquificae -related nifH gene lineage in Japan hot springs ( Figure 3 ), but those related nifH gene sequences have stop codons in their amino acid sequences ( Nishihara et al, 2018b ), indicating they are pseudogenes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Thermocrinis -affiliated bacteria may not have nitrogen fixation ability in some hot springs. This phenomenon can be explained by the fact that some Thermocrinis species living in YNP hot springs may obtain nifH gene from coexisting diazotrophs such as Hydrogenobacter through horizontal gene transfer that was speculated to occur among diazotrophs ( Koirala and Brözel, 2021 ) or prokaryotes in hot springs ( Zhu et al, 2019 ; Li et al, 2021 ; Qi et al, 2021 ). In addition, there was one unique Aquificae -related nifH gene lineage in Japan hot springs ( Figure 3 ), but those related nifH gene sequences have stop codons in their amino acid sequences ( Nishihara et al, 2018b ), indicating they are pseudogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Helarchaeota species encodes the complete set of enzymes allowing these archaea to perform methanogenesis or alkanotrophy under some conditions. 86 89 , 91 The alkane oxidation would rely on an association with sulfate-reducing bacteria. 92 …”
Section: Discovery and Diversity Of Coenzyme M-dependent Alkanotrophi...mentioning
confidence: 99%
“…Helarchaeota species encodes the complete set of enzymes allowing these archaea to perform methanogenesis or alkanotrophy under some conditions. [86][87][88][89]91 The alkane oxidation would rely on an association with sulfate-reducing bacteria. 92 In the mentioned methanogens and alkanotrophs, the alkane chemistry is supposed to be performed by ACRs.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative genomic analysis is an effective approach to illuminate the evolution and habitat adaptation mechanism of microorganisms ( 14 16 ) and the diverse metabolic capabilities of strains within the same species isolated from different habitats ( 17 ). Five Clostridium beijerinckii strains were isolated from pit mud, and comparative genomics of these strains and C. beijerinckii from other habitats showed that hundreds of genes were shared only by strains isolated from pit mud ( 18 ).…”
Section: Introductionmentioning
confidence: 99%